Sensor Web Service: A Geographical Information System (GIS)Based Model for Dependable Fire Detection in Forests (International Journal of Food and Nutritional Sciences, 2019)
Current emergency scenarios around the globe indicate that there is a tendency for theoccurrence of usual disasters to rise in the future. Thus, innovative methods of alternativemanaging have been very popular lately. All occurrences that jeopardise the regular operationof businesses and services, put lives or property at risk, or jeopardise the stability of the stateare considered emergency events. Hazardous events include any circumstances brought on byintensities, eruptions, technology failures, auto mishaps, extremist assaults, and thetransportation of dangerous goods